Satisficing in UIUX Design: A Theoretical Review Towards E-Commerce Users' Behavior - Indira Febriany; Nurwahyudi, Salsabillah Putri (Universitas Multimedia Nusantara, 2025)
Satisficing is one of the users’ behavioral patterns in decision-making. In which users tend to choose a “good enough” option compared to an optimal one. In the context of e-commerce UI/UX design, which has been facing challenges such as choice overload, it became important to understand this behavior, since the process of satisficing can happen quickly. This process might influence users’ perception of interface usability and aesthetics, also affecting users’ loyalty to the platform. The aim of this research is to study the characteristics of the user’s satisficing behavior and its implications for UI/UX design. This research adopts a qualitative approach through synthesis from literature studies such as scientific articles, books, official reports, and professional articles. The results show that there are two users’ satisficing behavior characteristics in the e-commerce UI/UX design context. Interface navigation satisficing, and purchase decision satisficing. However, both characteristics share similar motivations and solutions. An efficient, simple, and straightforward interface design can help both satisficing behaviors, and classic aesthetics and informative visual presentation can reduce the user’s cognitive process and elevate usability perception. This research recommends several interface design implementations that help users achieve goals with minimum time and effort, such as recommendation features, clear and intuitive navigation, and consistent visual presentations. Keywords: aesthetic, UI/UX design, user behavior, satisficing, usability